2014
DOI: 10.1074/jbc.m114.569178
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Export Protein of H5N1 Influenza A Viruses Recruits Matrix 1 (M1) Protein to the Viral Ribonucleoprotein to Mediate Nuclear Export

Abstract: Background: NEP stimulates viral RNA synthesis and nuclear vRNP export. Results: NEP is required to stabilize M1-vRNP binding for nuclear export. Deletion of the last three amino acids of NEP abrogates nuclear export and the polymerase-enhancing function of NEP. Conclusion:The polymerase-enhancing function and the nuclear export function of NEP are linked functionally. Significance: This study provides new insights into the assembly of the nuclear export complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…Mutations in NES1 inhibit virus recovery by reverse genetics and strongly impede vRNP nuclear export 84 ; whereas mutations in NES2 do not abolish virus recovery but severely impair viral growth kinetics and reduce the rate of vRNP nuclear export in infected cells 85 . Although these observations provide strong evidence of a role for NEP in vRNP nuclear export, no direct interaction between full-length NEP and the vRNP complex has been established 83,8689 . However, since NEP can interact directly with the M1 protein 86,90 , which in turn interacts with vRNPs 80 , a ‘daisy-chain model’ for influenza vRNP nuclear export has been proposed, whereby NEP acts as an adaptor between the CRM1 nuclear export pathway and M1-vRNP complexes (Figure 4).…”
Section: Nuclear Export Of Progeny Vrnpsmentioning
confidence: 73%
See 1 more Smart Citation
“…Mutations in NES1 inhibit virus recovery by reverse genetics and strongly impede vRNP nuclear export 84 ; whereas mutations in NES2 do not abolish virus recovery but severely impair viral growth kinetics and reduce the rate of vRNP nuclear export in infected cells 85 . Although these observations provide strong evidence of a role for NEP in vRNP nuclear export, no direct interaction between full-length NEP and the vRNP complex has been established 83,8689 . However, since NEP can interact directly with the M1 protein 86,90 , which in turn interacts with vRNPs 80 , a ‘daisy-chain model’ for influenza vRNP nuclear export has been proposed, whereby NEP acts as an adaptor between the CRM1 nuclear export pathway and M1-vRNP complexes (Figure 4).…”
Section: Nuclear Export Of Progeny Vrnpsmentioning
confidence: 73%
“…However, since NEP can interact directly with the M1 protein 86,90 , which in turn interacts with vRNPs 80 , a ‘daisy-chain model’ for influenza vRNP nuclear export has been proposed, whereby NEP acts as an adaptor between the CRM1 nuclear export pathway and M1-vRNP complexes (Figure 4). Recent data suggests that a more refined model – in which NEP simultaneously interacts with M1, the PB1 subunit of the vRNP-associated polymerase complex, and the CRM1 nuclear export receptor 89 – may be necessary to explain the mechanism of vRNP nuclear export; further work is needed to clarify this process. Additionally, whether NEP remains associated with vRNP complexes that have been transported to the cytoplasm is currently unknown.…”
Section: Nuclear Export Of Progeny Vrnpsmentioning
confidence: 99%
“…M2 protein mediates nuclear transport of virus ribonuclear protein complexes41. M2 protein has also been shown to alter membrane curvature and assist in the budding of the virus4243, therefore the observed reduction of M2 protein expression could lead to a diminished assembly and release of viral particles.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a recent study suggested that influenza polymerase can adopt an alternative configuration depending on which kind of viral RNA (vRNA or cRNA) is bound (Thierry et al, 2016). In addition, NEP was also found to directly interact with the viral polymerase associated with vRNPs, in an M1-dependent manner (Brunotte et al, 2014), leaving open the possibility of a direct interaction between NEP and the viral polymerase associated with cRNPs in navigating cRNP nuclear export. Further analysis will be required to fully understand the cRNP nuclear export process, as well as its biological functions in the cytosol.…”
Section: Discussionmentioning
confidence: 99%